Studying m6A in the brain: a perspective on current methods, challenges, and future directions - Tegowski, Matthew; Meyer, Kate D. (Frontiers in Molecular Neuroscience, 2024)
A major mechanism of post-transcriptional RNA regulation in cells is the addition of chemical modifications to RNA nucleosides, which contributes to nearly every aspect of the RNA life cycle. N 6 -methyladenosine (m 6 A) is a highly prevalent modification in cellular mRNAs and noncoding RNAs, and it plays important roles in the control of gene expression and cellular function.Within the brain, proper regulation of m 6 A is critical for neurodevelopment, learning and memory, and the response to injury, and m 6 A dysregulation has been implicated in a variety of neurological disorders. Thus, understanding m 6 A and how it is regulated in the brain is important for uncovering its roles in brain function and potentially identifying novel therapeutic pathways for human disease. Much of our knowledge of m 6 A has been driven by technical advances in the ability to map and quantify m 6 A sites. Here, we review current technologies for characterizing m 6 A and highlight emerging methods. We discuss the advantages and limitations of current tools as well as major challenges going forward, and we provide our perspective on how continued developments in this area can propel our understanding of m 6 A in the brain and its role in brain disease.